Comprehensive genomic profiling of different subtypes of nasopharyngeal carcinoma reveals similarities and differences to guide targeted therapy. Issue 18 (5th June 2017) - Ali, Siraj M.; Yao, Ming; Yao, Jicheng; Wang, Jing; Cheng, Yuwei; Schrock, Alexa B.; Chirn, Gung‐Wei; Chen, Hui; Mu, Shuo; Gay, Laurie; Elvin, Julia A.; Suh, James; et al.
Abstract : BACKGROUND: To date, no targeted therapy has been approved for nasopharyngeal carcinoma (NPC), and this underscores the need for an in‐depth understanding of clinically relevant genomic alterations (CRGAs). METHODS: Comprehensive genomic profiling was performed for 190 NPC patients, including 20 patients with nasopharyngeal adenocarcinoma (NPAC), 62 patients with nasopharyngeal squamous cell carcinoma (NPSCC), and 108 patients with nasopharyngeal undifferentiated carcinoma (NPUC). The associations of genes and pathways with subtypes, Epstein‐Barr virus (EBV) infections, and the tumor mutation burden (TMB) were statistically evaluated. RESULTS: Although the overall rates of genomic alterations were similar, the 3 NPC subtypes exhibited different mutational landscapes. Notably, mutations in a proven‐treatable target gene, isocitrate dehydrogenase 2 ( IDH2 ), were significantly associated with NPUC but not with NPAC or NPSCC. The top 5 ranked CRGAs included CDKN2A (29%), IDH2 (16%), SMARCB1 (7%), PIK3CA (6%), and NF1 (5%) in NPUC; CDKN2A (27%), PIK3CA (23%), FBXW7 (11%), PTEN (11%), and EGFR (8%) in NPSCC; and CDKN2A (20%), KRAS (15%), CCND1 (10%), MAP3K1 (10%), and NOTCH1 (10%) in NPAC. The incidence of EBV infections significantly correlated with the subtypes and with TP53, CDKN2A, and CDKN2B . The TMB status correlated with the subtypes and with LRP1B, FBXW7, and PIK3CA mutations as well as DNA repair, phosphoinositide 3‐kinase/mammalian target of rapamycin, and mitogen‐activated protein kinase pathways. CONCLUSIONS: These results indicate that different NPC subtypes harbor different CRGAs. Both EBV infections and the TMB are associated with the NPC subtypes as well as the alterations of individual genes and pathways. The high frequency of IDH2 mutations in NPUC may facilitate potential targeted therapy and will ultimately point to new therapeutic strategies. Cancer 2017;123:3628‐37. © 2017 American Cancer Society . Abstract : The incidence of nasopharyngeal carcinoma remains high in endemic regions; however, no targeted therapy has been approved for nasopharyngeal carcinoma. In a series of 190 cases of nasopharyngeal carcinoma, comprehensive genomic profiling has revealed that 3 nasopharyngeal carcinoma subtypes harbor different clinically relevant genetic alternations, and the high frequency of isocitrate dehydrogenase 2 mutations in nasopharyngeal undifferentiated carcinoma may facilitate the development of novel therapeutic strategies.